Minimally Invasive Diaphragm Plication for Acquired Unilateral Diaphragm Paralysis: A Systematic Review. Issue 3 (May 2022) - Gritsiuta, Andrei I.; Gordon, Matthew; Bakhos, Charles T.; Abbas, Abbas E.; Petrov, Roman V.
Objective: Diaphragm paralysis is a relatively uncommon entity that can be both congenital and acquired in nature. While commonly asymptomatic, it can also cause a significant decrease in pulmonary function and reserve, particularly in patients with underlying pulmonary diseases. Our aim was to summarize the current literature regarding the minimally invasive techniques used in the surgical correction of acquired diaphragm paralysis via traditional and robotic minimally invasive approaches.Methods: We conducted a systematic review of available literature using the Cochrane methodology and reported findings according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards.Results: A total of 6, 561 citations were identified through initial database and reference searches, of which 90 articles met the inclusion criteria for review. After further assessment, 33 appropriate full-text studies were selected for the review. Of the selected publications, the majority represented case reports and single-center retrospective studies with level of evidence 4. Only 1 level 2b study (individual cohort study) was identified, comparing minimally invasive and open approaches.Conclusions: Each of the minimally invasive approaches has its unique benefits and disadvantages, which are summarized and delineated in this article. Ultimately, no preferred method of diaphragm plication for diaphragm paralysis can be recommended at this time based on clinical data. The choice of procedure and surgical approach continues to be selected based on the surgeon's experience and preference.